Analysis of quorum sensing-dependent virulence factor production and its relationship with antimicrobial susceptibility in Pseudomonas aeruginosa respiratory isolates - KARAHASAN, AYŞEGÜL (ELSEVIER SCI LTD, 2010)
P>Pseudomonas aeruginosa is an opportunistic pathogen causing severe respiratory infections. The pathogenesis of these infections is multifactorial and the production of many virulence factors is regulated by quorum sensing (QS), a cell-to-cell communication mechanism. The two well defined QS systems in P. aeruginosa, the las and rhl systems, rely on N-acyl homoserine lactone signal molecules, also termed autoinducers. We assessed the activity of QS-dependent virulence factors (including elastase, alkaline protease, pyocyanin and biofilm production) in respiratory isolates of P. aeruginosa and their relationship with antimicrobial susceptibility. We identified sixteen isolates displaying impaired phenotypic activity; among them, eleven isolates were also defective in autoinducer production, and therefore considered QS-deficient. Six of the QS-deficient isolates failed to amplify one or more of the four QS regulatory genes (lasI, lasR, rhlI, rhlR) with PCR: one isolate was negative for rhlR, two isolates were negative for rhlI and rhlR and three isolates were negative for all four genes. The isolates that were negative for virulence factor production were generally less susceptible to the antimicrobials and statistically significant correlations were observed between the lack of elastase production and resistance to piperacillin and ceftazidime; between failure in alkaline protease production and resistance to tobramycin, piperacillin, piperacillin-tazobactam, cefepime, imipenem and ciprofloxacin; and between failure in pyocyanin production and resistance to amikacin, tobramycin, ceftazidime, ciprofloxacin and ofloxacin. The results obtained indicate that, despite the pivotal role of QS in the pathogenesis of P. aeruginosa respiratory infections, QS-deficient strains are still capable of causing infections and tend to be less susceptible to antimicrobials.
Keywords: Antimicrobial susceptibility; Pseudomonas aeruginosa; quorum sensing; virulence; MULTIDRUG EFFLUX SYSTEM; TO-CELL SIGNALS; FACTOR EXPRESSION; CYSTIC-FIBROSIS; ELASTASE; GENES